Case report: dysgeusia, strawberry tongue, and psoriatic eruptions after combination treatment with adalimumab, sulfasalazine, and etoricoxib for ankylosing spondylitis - Cui, Binglin; Lin, Jing; Huang, Yuanchun; Zhu, Huachen; Zou, Jinbo; Qin, Jiesheng; Pan, Hui; Chen, Jian (Frontiers in Medicine, 2025)
BackgroundTumor necrosis factor blockers can suppress immune system and lead to various adverse drug reactions, including deaths. We present a rare case of dysgeusia, strawberry tongue, and psoriasis-like eruptions after simultaneous administration of adalimumab, sulfasalazine, and etoricoxib.Case descriptionA 36 year-old male with ankylosing spondylitis presented with progressive loss of taste for 3 months and rashes on his upper trunk for 5 days. He had been receiving adalimumab, sulfasalazine, and etoricoxib for 9 months. After self-discontinuing the medicines, the rashes gradually subsided. On examination, swollen and red strawberry tongue were noticed. Acinetobacter pittii was isolated by sputum culture. The patient refused any treatment. During follow-up, recurrent dispersed papules/macules and desquamation appeared on his upper trunk, with erythema and erosion in umbilical region. Subsequently, generalized scalp erythema, exudates, scabs, hair bundles, redness and desquamation behind ears occurred. The tongue, taste, and skin lesions resolved sequentially and steadily until complete recovery.OutcomeHe remained in remission during 4 years follow-up. The total course of disease was around 10 months.DiscussionClinicians should be cautious of the adverse drug reactions/events due to adalimumab, sulfasalazine, and etoricoxib. Rational use of medicines is advocated.